Mediating Effects of Motivation on the Factors Affecting Hawker Food Entrepreneurs Intention: A Study among University Hospitality Chinese Students - LEONG, Tan Poh; PAIM, Laily Hj (Journal of Advanced Research in Management; Vol 7 No 1 (2016): JARM Volume VII Issue 1(13) Summer 2016, 2017)
Past scholars have focused on mostly business and entrepreneurial undergraduate students. There is a poor understanding of motivation (MA) factor as mediating variable explaining the relationships among various factors such as subjective norms (SN), barriers (BA), and hawker entrepreneurial intention among young Chinese hospitality undergraduate students. Therefore, this paper explores the relationships between motivation variables and the variables of Theory Reason Action (TRA) associated with Chinese university hospitality students’ intention to become hawker food entrepreneurs. The research model reflects the effects of MA, SN and BA on TRA constructs have been proposed. In total, 141 cases were gathered from the survey. Structural equation modelling was used to measure the proposed theoretical research model. The result concluded that motivation discovered significantly support of this study but not subjective norm and barriers factor. The limitations in this study might have faults in responding as some respondents may have interest to work in a hotel rather than setting up as a hawker entrepreneur. Future research may investigate on those hospitality graduates that have already set up hawker entrepreneur this may prevent any mistake. The results of the study have contributed to the entrepreneurship body of new knowledge, especially in the Theory Reasoned Action, particularly in terms of hawker food entrepreneurial intention.